Anterior Cruciate Ligament Reconstruction Using Fixed Loop All-Inside (FLAI) Technique - Hesham Mohamed Gawish, M.D.; Mahmoud Hammam Hashish, M.Sc.; Mohamed Abd Elmonsef Elghaish, M.Sc. (Arthroscopy Techniques, 2023)
The aim of this surgical technical note is to provide a more secure option to prevent possible graft loosening with all-inside anterior cruciate ligament (ACL) reconstruction. A triple strategy is used. First, a fixed loop cortical device is used on the femoral side. Second, an internal brace augmentation for ACL graft is employed to prevent graft loosening during early postoperative period. Lastly, tying off the sutures of tibial adjustable loop after retensioning to secure its locking mechanism from slippage.